1984
DOI: 10.1149/1.2115542
|View full text |Cite
|
Sign up to set email alerts
|

Cathode Characteristics of Organic Electron Acceptors for Lithium Batteries

Abstract: Discharge and charge characteristics of cathode‐active materials for lithium batteries were studied. Electron acceptors of charge transfer complex with high electron affinity were examined as cathode‐active materials because they were expected to have high cell voltage. These electron acceptors are 2,4,7‐trinitro‐9‐fluorenone (TNF), 2,4,5,7‐tetranitro‐9‐fluorenone, 7,7,8,8‐tetracyanoquinodimethane, 9,10‐phenanthrenequinone, and 13 other compounds. Among these compounds, TNF showed the highest discharge capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 0 publications
3
62
0
Order By: Relevance
“…neglecting any differences in lithium ion chemical potential or surface potential, a similar value 25 is expected for the TCNQ electrode. Indeed, the value corresponds reasonably well to the value reported for the second discharge plateau (2.4-2.6 V) by Tobishima et al, as obtained for a battery containing TCNQ and acetylene black as cathode and lithium as anode 6 . Notably, application of this simple procedure 30 to evaluate the electrode potential of TCNQ directly with respect to lithium (work function 2.5-2.9 eV 34,35 ) yields a potential of 2.8-2.4 V vs. Li/Li + which fits quite well both for LiCoO 2 and TCNQ.…”
Section: Electrode Potentialsupporting
confidence: 91%
See 1 more Smart Citation
“…neglecting any differences in lithium ion chemical potential or surface potential, a similar value 25 is expected for the TCNQ electrode. Indeed, the value corresponds reasonably well to the value reported for the second discharge plateau (2.4-2.6 V) by Tobishima et al, as obtained for a battery containing TCNQ and acetylene black as cathode and lithium as anode 6 . Notably, application of this simple procedure 30 to evaluate the electrode potential of TCNQ directly with respect to lithium (work function 2.5-2.9 eV 34,35 ) yields a potential of 2.8-2.4 V vs. Li/Li + which fits quite well both for LiCoO 2 and TCNQ.…”
Section: Electrode Potentialsupporting
confidence: 91%
“…Investigations have been performed on various organic lithium insertion cathode materials, such as polypyrole and tetracyanoquinodimethane (TCNQ) 1,2,4,5 , some of them with very promising results. With a TCNQ composite 25 electrode a specific capacity of 263 mAh/g 2 could be reached with flat shaped charge-discharge curves 2,6 . During intercalation of lithium into a host material, lithium ions are incorporated at suitable locations in the host and electrons fill unoccupied electronic states of the host.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, such kinds of organic radical intermediates are generally unstable and could rapidly transform to inactive compounds by reacting with other molecules in the electrolyte or in between the radicals, which eventually leads to irreversibility of the redox process and thus results in disappointing rechargeability (Fig. 1a)2930. This phenomenon has long been investigated in the redox behaviour of carbonyl compounds.…”
mentioning
confidence: 99%
“…However, we have made an attempt to compare our work with studies reported on DDQ based batteries. Mostly, in few secondary Li-ion batteries, [21][22][23] and Mg-ion [24] batteries DDQ was used as cathode material. There are many reports on derivatives of quinone for flow battery applications.…”
Section: Electrochemical Performance Of Fe-ddq Primary Cellmentioning
confidence: 99%